Psychiatric diagnoses and cognitive impairment in pediatric multiple sclerosis. (April 2014) - Weisbrot, Deborah; Charvet, Leigh; Serafin, Dana; Milazzo, Maria; Preston, Thomas; Cleary, Rebecca; Moadel, Tiffany; Seibert, Michelle; Belman, Anita; Krupp, Lauren
Background: Pediatric multiple sclerosis (MS) represents approximately 5% of the MS population; information regarding clinical features is slowly accumulating. Cognitive and psychiatric impairments frequently occur, but remain poorly understood. Objectives: To describe psychiatric diagnoses among children with MS referred for psychiatric assessment and their relation to cognitive impairment. Methods: Forty-five pediatric MS patients (aged 8 to 17 years) were referred for outpatient psychiatric evaluation including a psychiatric interview (K-SADS), a clinician-based global assessment of functioning (Children's Global Assessment Scale, CGAS), a neurologic examination including the Expanded Disability Status Scale (EDSS), and a neuropsychological test battery. Results: The most common categories of psychiatric diagnoses were anxiety disorders ( n =15), attention deficit hyperactivity disorder (ADHD, n =12), and mood disorders ( n =11). Cognitive impairment was classified in 20/25 (80%) of patients meeting criteria for a psychiatric disorder versus 11/20 (55%) of those without psychiatric disorder ( p =0.08). Those diagnosed with anxiety or mood disorder had the highest frequency of cognitive impairment, with a significantly higher rate when compared with those with psychiatric diagnoses in other categories ( p =0.05). Conclusions: A variety of psychiatric diagnoses can occur in children with pediatric MS. Many of these children also had cognitive impairment, particularly those in the mood and anxiety groups.